Twitter-Based Discourse on Migrants in Russia: The Case of 2013 Bashings in Biryulyovo - Bodrunova, Svetlana Sergeevna; Litvinenko, Anna Alexandrovna; Gavra, Dmitry Petrovich; Yakunin, Aleksandr Vasilievich (International Review of Management and Marketing, 2015)
According to a number of scholars, Twitter possesses big potential to become a ‘crossroads of discourses' due to its openness, de-hierarchization, and spontaneity (Miller 2014, Shirky 2008). At the same time, substantial criticism has risen towards political and deliberative efficacy of Twitter (Fuchs 2013). The authors aim at analyzing the features of the Twitter-based agenda setting within the hybrid media system in Russia (Chadwick 2013, Bodrunova & Litvinenko 2013a). The research question is whether the use of Twitter in the Russian socio-political context potentially leads to the formation of the ‘crossroads of opinions' or, in contrast, to closing-up of political discussion and to further fragmentation of public discourse. The research focuses on structural and content aspects of discussion on anti-migrant bashings in Biryulyovo (Moscow) that happened in October 2013. Our research methods include automated vocabulary-based web crawling, word frequency analysis, manual coding of tweets, and interpretation of statistical data. Preliminary results suggest an unexpectedly high level of mediatization of the discussion; the hypothesis about the ‘crossroads' nature of the discussion on the Russian Twitter seems to be proven, which makes this platform differ from the Russian Facebook where, according to another recent study (Bodrunova & Litvinenko 2013b), political discussions are held mostly in closed-up communicative milieus, or ‘echo chambers' (Sunstein 2007). Keywords: Twitter, Russia, web crawling, social media, migrants, echo chambers JEL Classifications: O32; Z13